Radiation exposure of the interventional radiologist during percutaneous biopsy using a multiaxis interventional C-arm CT system with 3D laser guidance: a phantom study - Rathmann, Nils-Andreas; Bartling, Sönke; Haubenreisser, Holger; Schönberg, Stefan; Diehl, Steffen J. (British journal of radiology, 2015)
Objective: Evaluation of absolute radiation exposure values for interventional radiologists (IRs) using a multiaxis interventional flat-panel C-arm cone beam CT (CBCT) system with three-dimensional laser guidance for biopsy in a triple-modality, abdominal phantom. Methods: In the phantom, eight lesions were punctured in two different angles (in- and out-of-plane) using CBCT. One C-arm CT scan was performed to plan the intervention and one for post-procedural evaluation. Thermoluminescent dosemeters (TLDs) were used for dose measurement at the level of the eye lens, umbilicus and ankles on a pole representing the IRs. All measurements were performed without any lead protection. In addition, the dose-area product (DAP) and air kerma at the skin entrance point was documented. Results: Mean radiation values of all TLDs were 190 µSv for CBCT (eye lens: 180 µS, umbilicus: 230 µSv, ankle: 150 µSv) without a significant difference (p > 0.005) between in- and out-of-plane biopsies. In terms of radiation exposure of the phantom, the mean DAP was not statistically significantly different (p > 0.05) for in- and out-of-plane biopsies. Fluoroscopy showed a mean DAP of 7 or 6 μGym2, respectively. C-arm CT showed a mean DAP of 5150 or 5130 μGym2, respectively. Conclusion: In our setting, the radiation dose to the IR was distinctly high using CBCT. For dose reduction, it is advisable to pay attention to lead shielding, to increase the distance to the X-ray source and to leave the intervention suite for C-arm CT scans. Advances in knowledge: The results indicate that using modern navigation tools and CBCT can be accompanied with a relative high radiation dose for the IRs since detector angulation can make the use of proper lead shielding difficult.